A Proposed Mechanism for Financial Reporting on Sustainable Investment and Its Role in Achieving Value Added - Applied in the Iraqi Midland Refineries Company- - Ali, Mohammed Ataallah; Abdullah, Salman Hussein (Journal of Economics and Administrative Sciences, 2021)
The research aims to develop a proposed mechanism for financial reporting on sustainable investment that takes the specificity of these investments.To achieve this goal, the researcher used (what if scenario) where the future financial statements were prepared for the year 2026, after completion of the sustainable project and operation, as the project requires four years to be completed.The researcher relied on the results of the researchers collected from various modern sources relevant to the research topic and published on the internet, and the financial data and information obtained to assess the reality of the company's activity and its environmental, social, and economic impacts to formulate a proposed mechanism for accounting for Sustainable Investment.And the experimental approach was adopted to provide a proposed mechanism for financial reporting on sustainable investment per international accounting and reporting standards and then applied at the Iraqi Midland refineries company.There are three main findings from the research: the first finding shows the possibility of financing these projects, because this project may not generate significant economic returns (aims to achieve environmental and social returns as well), by configuring a sustainable reserve allocated to finance these projects. The second finding shows the possibility of presenting accounts for sustainable investment separately from traditional accounts (sustainability reserves, sustainable assets, sustainable revenues, sustainability expenses), as this classification can play an important role in the financial sustainability analysis. The third finding is the application of the proposed mechanism that contributes to increase the company's added value.The practical effects of the research are to encourage Iraqi companies (oil companies in particular) to invest in sustainable assets and develop a way to assess the sustainability of companies, because Iraq is one of the most Arab countries burning Gas flare. The researcher tried to highlight this project because it is the best example of sustainable investment that achieves economic returns (the sale value of recovered gases), social returns (protection of citizens living in the vicinity of the refinery) and environmental returns (reducing greenhouse gas emissions that contribute to global warming), where companies avoid investing in these assets because of their high cost and lack of expected financial return, and the relevant international organizations seek to promote this type of investment and develop appropriate tools, and this research comes in line with international trend.The concept of sustainable investment is a relatively recent one, where the originality of the current research shows in its attempt to present a proposed mechanism of financial reporting that supports this new type of investment due to the relative importance of this new type of investment